A novel arabidopsis vacuolar glucose exporter is involved in cellular sugar homeostasis and affects the composition of seed storage compounds - Poschet, Gernot; Büttner, Michael (Plant physiology, 2011)
Subcellular sugar partitioning in plants is strongly regulated in response to developmental cues and changes in external conditions. Besides transitory starch, the vacuolar sugars represent a highly dynamic pool of instantly accessible metabolites that serve as energy source and osmoprotectant. Here, we present the molecular identification and functional characterization of the vacuolar glucose (Glc) exporter Arabidopsis (Arabidopsis thaliana) Early Responsive to Dehydration-Like6 (AtERDL6). We demonstrate tonoplast localization of AtERDL6 in plants. In Arabidopsis, AtERDL6 expression is induced in response to factors that activate vacuolar Glc pools, like darkness, heat stress, and wounding. On the other hand, AtERDL6 transcript levels drop during conditions that trigger Glc accumulation in the vacuole, like cold stress and external sugar supply. Accordingly, sugar analyses revealed that Aterdl6 mutants have elevated vacuolar Glc levels and that Glc flux across the tonoplast is impaired under stress conditions. Interestingly, overexpressor lines indicated a very similar function for the ERDL6 ortholog Integral Membrane Protein from sugar beet (Beta vulgaris). Aterdl6 mutant plants display increased sensitivity against external Glc, and mutant seeds exhibit a 10% increase in seed weight due to enhanced levels of seed sugars, proteins, and lipids. Our findings underline the importance of vacuolar Glc export during the regulation of cellular Glc homeostasis and the composition of seed reserves.